Linking Narcissism, Motivation and Doping Attitudes in Sport: A Multilevel Investigation Involving Coaches and Athletes - Matosic, D.; Ntoumanis, Nikos; Boardley, I.; Stenling, A.; Sedikides, C. (Human Kinetics, 2016)
Research on coaching (Bartholomew, Ntoumanis, & Thøgersen-Ntoumani, 2009) has shown that coaches can display controlling behaviors that have detrimental effects on athletes' basic psychological needs and quality of sport experiences. The current study extends this literature by considering coach narcissism as a potential antecedent of coaches' controlling behaviors. Further, the study tests a model linking coaches' (n = 59) own reports of narcissistic tendencies with athletes' (n = 493) perceptions of coach controlling behaviors, experiences of need frustration, and attitudes toward doping. Multilevel path analysis revealed that coach narcissism was directly and positively associated with athletes' perceptions of controlling behaviors, and was indirectly and positively associated with athletes' reports of needs frustration. Additionally, athletes' perceptions of coach behaviors were positively associated-directly and indirectly-with attitudes toward doping. The findings advance understanding of controlling coach behaviors, their potential antecedents, and their associations with athletes' attitudes toward doping.